2020
DOI: 10.1016/j.jht.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy corresponds to wrist function after combined plating of distal radius fractures

Abstract: a b s t r a c tStudy Design: A prospective cohort single-center study. Introduction: Self-efficacy (SE) refers to beliefs in ones capabilities to organize and execute the courses of action required to produce given goals. High SE is an important factor for recovery from injury/illness; people who believe in their capability will more likely reach a good outcome.Purpose of the Study: The aim of this study was to examine if SE has an effect to physical functioning, pain and patient-rated wrist function three mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Self-efficacy plays a key role in disease treatment and rehabilitation (16)(17)(18). Studies have confirmed that self-efficacy plays a key role in postoperative functional recovery in patients with HF (17,18) and is also associated with the decline of healthrelated quality of life in older patients with fractures (19). Resilience is the ability to respond effectively and actively adapt to the environment when individuals face adversity, trauma, or different forms of pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy plays a key role in disease treatment and rehabilitation (16)(17)(18). Studies have confirmed that self-efficacy plays a key role in postoperative functional recovery in patients with HF (17,18) and is also associated with the decline of healthrelated quality of life in older patients with fractures (19). Resilience is the ability to respond effectively and actively adapt to the environment when individuals face adversity, trauma, or different forms of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is defined as the belief people have that they can perform the behaviors necessary to achieve their goals, which determines how individuals feel and think and facilitates their beliefs and behaviors (16). Self-efficacy plays a key role in disease treatment and rehabilitation (16)(17)(18). Studies have confirmed that self-efficacy plays a key role in postoperative functional recovery in patients with HF (17,18) and is also associated with the decline of healthrelated quality of life in older patients with fractures (19).…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy or self-supervised exercise programs are commonly recommended as a rehabilitation strategy after such injuries [16][17][18]. Previous research has shown that practical constraints such as time, costs and travel distance lead to a low adherence to physiotherapy referrals and exercises [19,20]. Treatment adherence to homebased, self-supervised exercise programs is equally low, mainly due to a lack of monitoring and feedback to patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of DRF in females is signi cantly greater than in males incorporating the menopause as a responsible factor leading to osteoporosis associated with reduced bone density showing peak between the age group of 60 and 70 (Gutiérrez-Espinoza et al, 2017). Early rehabilitation concentrate on oedema management, pain reduction as well as shoulder and nger motions (Björk et al, 2020). The therapeutic methods applied to attain these goals may be categorized as active or passive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical management options include closed reduction and application of a cast, percutaneous K-wires, open reduction and internal xation with plates, or external xation according to the patient requirements(Vaghela et al, 2020). Following DRF, many factors manipulate the recovery of the patient implying the age, gender, site and extent of the injury, management line followed to manage the respective injury, compensations, patient's education regarding the condition, radial shortening, and intra-articular involvement(Björk et al, 2020). Patients generally recover within 3-6 months to the maximum range of motion, strength and function whether managed conservatively or surgically.Patients with DRF after a duration of immobilisation are often referred for physiotherapy.…”
mentioning
confidence: 99%